Characteristics of Sugarcane Bagasse Fiber (Saccharum officinale) Reinforced Polypropylene Composites - Nanang Masruchin; Wida B. Kusumaningrum; Ismadi Ismadi; Subyakto Subyakto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
This research investigates utilization of bagasse to make biocomposite with thermoplastic polypropylene by adding maleated acid anhydride (MAPP) as a compatibilizer and several fiber treatments. The blending was performed on Laboplastomil mixer, and sample was prepared by hot press. The effects of fiber loading (20, 30, 40 and 50% by weight), washing with 2% detergent, 5% alkali treatment and MAPP percentage (1, 3, 5, and 7.5% by weight), on the mechanical and physical properties were evaluated. The effect of elevated temperature on biocomposite was revealed by using thermogravimetric analysis under inert condition. Good compatibility and stress transfer was performed on 40% bagasse with alkali treatment by adding 5% MAPP; and the results on mechanical properties was better than detergent treatment. It showed that the mechanical properties for flexural strength, flexural modulus, tensile strength and tensile modulus increase by about 56.64%, 151.78%, 0.07% and 133.33%, respectively than pure matrix. Maleated acid treatment also shows the tendency to decrease water absorption. Alkali treatment also revealed to increase the thermal stability of composite, while the presence of MAPP decreased the thermal stability of composite. But it does not affect when processing is conducted below 225°C.